EUROPEAN OAK’S GROWTH RINGS PROPERTIES: DENSITY DISTRIBUTION AND THERMAL BEHAVIOR ANALYSIS OF EARLY – AND LATEWOOD (Innovation in Woodworking Industry and Engineering design, 2026)
Last decades wood is promoted as building material. Unprotected wood exposed to outdoor conditions undergoes a variety of degradation induced essentially by fungi attacks. Heat treatment of wood by mild pyrolysis (180°C